WELDING OF ADDITIVE MANUFACTURED ALSI10MG: USING LASER WELDING IN A VACUUM FOR HIGH QUALITY WELD SEAMS — A NEW APPROACH TO WELDING LPBF MANUFACTURED ALSI10MG - Schwarz, Alexander; Schleser, Makus; Gerhards, Benjamin; Popoola, Patrica; Gebhardt, Andreas (The South African Journal of Industrial Engineering, 2021)
Metal additive manufacturing has evolved to a manufacturing process used in different industries. Especially in highly complex applications with small batches, such as aerospace or tooling, laser powder bed fusion (LPBF) has become established. But one of its major limitations is the size of the build chamber, which is limited to around 800 x 400 x 500 mm for the largest machine that is currently available. One solution to overcome this size limitation is to weld additive manufactured parts. While it has been proven for different materials that conventional welding processes can be applied to LPBF manufactured parts, the resulting weld seam quality for AlSi10Mg is still insufficient. By using laser welding in a vacuum, which is a newly developed and highly efficient laser welding process, the quality of the weld seams, especially in terms of porosity, can be improved. This technology is used to produce weld seams that are then tested for their mechanical properties. Finally, a solution for combining LPBF parts with conventional aluminium alloys is presented.